Gender Equality Messages in Film Marlina The Murderer In Four Acts - Husen Mulachela; Aurelius RL Teluma; Eka Putri Paramita (Universitas Mataram, 2019)
This research trying to analyze the meaning of symbols in the film Marlina The Murderer in Four Acts based on the indicators of gender equality namely, access, participation, control, and benefits. The unit of analysis in this study includes the audio and visual elements that exist in a selected scene for later analysis using the Roland Barthes semiotic method known as the